Zoning Policy Implementation and Its Impact on the Acceptance of Madrasah Aliyah Students (Public and Private) in Bekasi Regency - Marlina, Yuli; Muliawati, Teti; Kusmayadi, Andri; Fatimah, Elva Siti (EDUTEC : Journal of Education And Technology, 2023)
The purpose of this study is to ascertain how zoning regulations are implemented and how they affect to Madrasah Aliyah in Bekasi Regency's decision in accept private students. The method used in this study is a quantitative method, while data analysis used a simple regression approach. According to the study's findings, there was a 50% favorable impact on the Bekasi Regency's zoning policy on the admission of students to private Islamic high schools. Where the t table value is 1.796, while t count is obtained from SPSS data processing of 1.918 > 1.796 (t table) it can be concluded that the t-count is greater than the t-table value, this means that Ho is rejected and Ha is accepted.